ARCHITECTURE OF SOCIAL BUSINESS CENTERS: FROM ANALYSIS OF PROBLEMS TO APPROACHES OF THEIR SOLUTIONS - , Н. І., М. І. (Municipal economy of cities. Series: «Economy science», 2017)
The tendencies of the formation of social and business centers at the present stage of the development of society in various urban structures - from central to peripheral ones - are considered. On the basis of problem-interdisciplinary research, the hierarchy of problems of the urban environment and the methodology for their solution are singled out at the stages of architectural design. At the same time, environmental requirements are taken into account. Also, the aspects of preservation of the historical environment of the city and energy saving technologies are taken into account in the architectural project. Formation of an architectural object, whether part of a city or a building, depends directly on the surrounding urban environment. That is, the existing architectural environment, its problems and modern requirements for it, "dictate" this or that decision of the architectural object. The article presents experimental master's works, which reveal specific problems of the city of Kharkov and their solution in the applied part - in complex architectural projects. This makes it possible to predict complex processes of dynamic transformation of architectural space and even at the design stage to influence the harmonious development of the city in an urbanized environment. Keywords: social and business centers, urban environment, problem-interdisciplinary research, energy-efficient technologies, "mirror" creativity and consumption, "green" construction.